Automorphic forms of higher order - Deitmar, Anton; Diamantis, Nikolaos (Oxford University Press for the London Mathematical Society, 2009)
In this paper a theory of Hecke operators for higher-order modular forms is established. The definition of higher-order forms is extended beyond the realm of parabolic invariants. A canonical inner product is introduced. The role of representation theoretic methods is clarified and, motivated by higher-order forms, new convolution products of L-functions are introduced.